Dural arterial prostheses: Preliminary study - Altieri, Carlos; Sanguinetti, Julio; D'Espagne, Paul; Miraglia, Domingo (Cirugía del Uruguay, 1975)
The authors study the behaviour of the dura mater as prosthetic material in the reconstruction of arterial segments in different anatomical locations. 6 prosthesis, manufactured with dura mater were placed in 5 dogs, substituting, either partially or totally, segments of the aorta, carotid and femoral arteries. Angiographic and pathological studles in different evolutive moments (until 14 months after surgery) show the functional and biological aptitudes of the tested material: good mechanical qualities, perfect endothellzation, lack of rejection phenomena.